Is Legislation Governing Tertiary Work Experience Effective? Exploring the Regulatory Role Played by Australian Universities. (March 2022) - Hewitt, Anne
This article extends current understandings of regulation of tertiary education, in particular, work experience undertaken by tertiary students, by contributing a 'law in practice' analysis of the effect of the existing regulatory regime on work integrated learning practice within Australian universities. It considers how Australian universities are responding to, implementing, or overlooking the formal regulatory framework regarding work experience placements. The analysis is informed by data gathered in a series of 68 semi-structured interviews conducted with individuals from 15 universities around Australia and provides unique insights into how Universities are acting as regulators in the broad sense of the word. Understanding the enforcement of educational regulation is important, because it is the only national tool directed to ensuring work experience opportunities afford real learning which will facilitate skills development and increase future employment opportunities and are equitable and safe for student participants.